The Christians of Kerala history, belief, and ritual among the Yakoba - Visvanathan, Susan (Delhi ; Oxford : Oxford University Press, 1993)
This text is an attempt to understand the practice of Christianity in a small neighbourhood in Kerala, and argues that people's interpretations of Christianity constitute a powerful mode of cultural expression and societal flexibility.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Syriac Christians -- India -- Kerala; Christianity -- India -- Kerala; Kerala (India) -- Religion; Christianity and other religions -- Hinduism; Hinduism -- Relations -- Christianity